A Novel Multi-Agent Approach to control Service level Agreement Violations in Cloud Computing - et. al., A.Kannaki @ Vasantha Azhagu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud computing becomes popular platform since it offers all key resources from infrastructure to software as on-demand service to the customers through internet. Moreover, its virtualized physical resources are dynamically scalable to meet any surge in the workload. Cloud Service Providers (CSPs) give assurance to quality of their services based on their customer requirements in the form a contract called Service Level Agreement (SLA). However, SLA violations affect the business operations of both CSP and cloud customers as CSP providers must compensate the loss of their customer. This paper presents new agent based architecture which minimizes the SLA violation automatically and hereby improves the trust of all stakeholders. It uses multiple many agents like coordinating agent, negotiation agent and arbitrator agent to control the SLA violations. The performance of the proposed work is assessed using CloudSim and Java Agent DEvelopment Framework (JADE). The experimental results reveal that the proposed multi agent based approach performs better than the existing approaches in terms of profit, penalty, and cost execution time and successful execution rate.